Implementasi Perpres Percepatan Manajemen Penangulangan Kemiskinan Melalui Program Keluarga Harapan Di Kelurahan Rawa Makmur Permai Kota Bengkulu - Marsidi Marsidi; Herman Ginting; Askani Askani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This research is motivated by the increasing poverty rate in Rawa Makmur Permai Village and to improve the welfare of the local community, the Implementation of Presidential Regulation No. 15 of 2010 concerning the acceleration of poverty reduction through the Family Hope Program (PKH) in Rawa Makmur Permai Village was implemented. This study aims to determine the communication and bureaucracy implementation of Presidential Regulation No. 15 of 2010 concerning Poverty Alleviation to reduce poverty through the PKH Program in Rawa Makmur Permai Village and to find out the inhibiting factors in the implementation of Presidential Regulation No. 15 of 2010 in tackling poverty through the PKH program in Rawa Makmur Permai Village. The type of research in this study is qualitative with descriptive methods, for data sources using primary and secondary data using collection techniques, namely observation, interviews and documentation. After the interviews were conducted with the selected informants, the researcher would process the data using data analysis techniques, namely data collection, data reduction, data presentation, and conclusion. The results showed that communication and bureaucracy in the implementation of Presidential Regulation no. 15 of 2010 concerning the acceleration of poverty reduction to reduce poverty through the PKH Program in Rawa Makmur Permai together has a real influence and is the most important thing in the proper implementation of Presidential Decree No. 15 of 2010 concerning the acceleration of poverty alleviation to reduce poverty through the PKH Program in Rawa Makmur Permai. Communication and bureaucracy went well in RT 10, Rawa Makmur Permai. The availability of resources, especially human resources in carrying out the PKH Program is a factor that needs to be considered to realize the PKH program in Rawa Makmur Permai Village. Especially for the 3 (three) RTs which are the focus of research, sufficient human resources make the implementation of the response to be carried out properly with the presence of resources that work well before and after the provision of assistance. The inhibiting factors in the implementation of Presidential Regulation No. 15 of 2010 concerning the acceleration of poverty alleviation to reduce poverty through the PKH Program in Rawa Makmur Permai, namely the role of companion and coordination between related agencies which have not all worked well.